Breast Self-Examination (BSE) and attitude towards Breast Self-Examination (BSE) among women: a narrative review - ., Najwa Izzati; Al-Alela, Omar; Elkalmi, Ramadan Mohamed Mahmod; Siddiqui, Mohammad Jamshed Ahmad; Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Shamsudin, Siti Hadijah; Jamshed, Shazia Qasim (Journal of Pharmaceutical and BioSciences, 2013)
The prevalence of breast cancer augments together with the technical global development and modernization. Breast carcinoma is one of the leading causes of death in women. A literature search was conducted in July-October 2012 to explore the published articles regarding awareness of breast cancer and breast self-examination (BSE) in Asian settings. This review included studies which measured knowledge regarding breast cancer and studies on attitude, practice and barriers to breast self-examination by using qualitative (one-to-one interview, concept mapping) or quantitative methods (cross-sectional survey) or both. The search was initiated through several keywords: breast cancer, breast cancer awareness, statistics of breast cancer, breast self-examination, etc. Other included electronic databases were Science Direct, Sage, Life Science, Springer Link, BioMed Central, Proquest and EBSCOhost. The search was limited to full paper articles published in English between 2000- 2012 and only seventeen full text articles were included in review. The studies included in review are from Hong Kong, Australia, UK, Iran, Qatar, Nigeria, and Malaysia. This review highlights the awareness of breast cancer by means of BSE and attitude towards BSE. Proactive educational measures by healthcare professionals and mass media campaigns are therefore suggested to enhance BSE screening and breast cancer awareness among women.